2001
DOI: 10.1016/s0927-0256(00)00130-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of microcrack healing in copper

Abstract: The molecular dynamics method is used to simulate microcrack healing during heating or/and under compressive stress. A center microcrack in Cu crystal could be sealed under a compressive stress or by heating. The role of compressive stress and heating in crack healing was additive. During microcrack healing, dislocation generation and motion occurred. If there were pre-existed dislocations around the microcrack, the critical temperature or compressive stress necessary for microcrack healing would decrease, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In all cases, periodical boundary condition [26,36] was adopted in z direction. The initial velocity was the Maxwell-Boltzmann distribution corresponding to a given temperature.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, periodical boundary condition [26,36] was adopted in z direction. The initial velocity was the Maxwell-Boltzmann distribution corresponding to a given temperature.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…MD simulation was conducted to study crack healing in Al [25] and Cu crystals [26], both of which are face centered cubic (FCC). Dislocation generation and motion occur during crack healing.…”
Section: Introductionmentioning
confidence: 99%
“…8, an excellent process is found that the crack branching is healed in the propagation of crack. Early experimental studies have shown that the microcrack in metal materials could be healed through the control of temperature effect and several simulation results [32] in copper or aluminum also elucidate this particular process during heating or compressive stress.…”
Section: Instability Analysismentioning
confidence: 99%
“…The simulation results showed that a center penetrating microcrack in Cu or Al crystal could be healed under a compressive stress or by heating, and the role of compressive stress and heating in crack healing was additive [10,11]. During microcrack healing, dislocation emission and motion occurred and pre-existed dislocation could decrease the critical temperature or compressive stress necessary for microcrack healing [10,11]. In these simulations, however, a periodic boundary condition was used, and there was a quasi-three-dimensional simulation involving only 6 Â 10 3 atoms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular dynamics method was used to simulate microcrack healing during heating or/and under compressive stress [10,11]. The simulation results showed that a center penetrating microcrack in Cu or Al crystal could be healed under a compressive stress or by heating, and the role of compressive stress and heating in crack healing was additive [10,11].…”
Section: Introductionmentioning
confidence: 99%